Peran Suri Tauladan Guru Dalam Pembinaan Akhlak Siswa Sekolah Menengah Pertama Islam Terpadu - Mushthofa; Mujiburrohman; Abdullah, Mu'in (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
This research aims to (1) Describe the role of teacher role models at SMP IT Mutiara Insani Delanggu (2) Describe the role of teacher role models in student moral training (3) Describe the factors inhibiting teacher role models. This research is field research. The approach used by the author in this research is a qualitative descriptive approach. Data collection was carried out using interviews, observation and documentation methods. The results of the research show that (1) the role of teacher role models at SMP IT Mutiara Insani is very influential on the formation of student morals because morals themselves are a commendable trait that is highly prioritized in schools (2) teacher role models in student moral training are influential and can have a positive effect on development students (3) factors inhibiting teacher role models, namely the lack of totality in providing moral training to students, parents at home in giving direction to their children, social factors and environmental factors which are very influential in forming good character.